О сумме почти абелевой алгебры Ли и алгебры Ли, конечномерной над своимцешром - Петравчук, А.П. (Український математичний журнал, 1999)
Доведено, що алгебра Лі L над довільним полем, що розкладається в суму L=А+В майже абелевої підалгебри A і скінчеінновимірної над своїм центром підалгебри 5, майже розв'язна, тобто містить розв'язний ідеал скінченної ковимірпості. Зокрема, сума абелевої та майже абелевої алгебр Лі є майже розв'язною алгеброю Лі. We consider a Lie algebraL over an arbitrary field that is decomposable into the sumL=A+B of an almost Abelian subalgebraA and a subalgebraB finite-dimensional over its center. We prove that this algebra is almost solvable, i.e., it contains a solvable ideal of finite codimension. In particular, the sum of the Abelian and almost Abelian Lie algebras is an almost solvable Lie algebra.